Literatur Review: Fraud dan Manipulasi Akuntansi dalam Konsolidasi - Ramadhan, Mohammad Rizki; Veronica, Tasya Amelia; Mappadang, Agoestina (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify patterns of fraud and accounting manipulation in consolidated financial statements and to develop detection indicators based on theory and technological approaches. Using a systematic literature review method on reputable journals published between 2018 and 2024, this research examines the risks of fraud arising from the complexity of group structures and weak implementation of reporting standards such as PSAK 4. The synthesis reveals that fraud in consolidation commonly occurs through improper elimination of intercompany transactions, unjustified consolidation of entities, and limited disclosure of related party transactions. The fraud pentagon theory is applied to classify fraud drivers, while red flags and machine learning-based findings are used to develop fraud detection indicators. This study concludes with five fraud indicator categories specific to consolidation reports and recommends the integration of detection technology to enhance audit and oversight effectiveness.